2009
DOI: 10.1021/ja808402e
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis of the Potent Anticancer Aglaia Metabolites (−)-Silvestrol and (−)-Episilvestrol and the Active Analogue (−)-4′-Desmethoxyepisilvestrol

Abstract: Total synthesis of the anticancer 1,4-dioxane containing natural products silvestrol (1) and episilvestrol (2) is described by an approach based on the proposed biosynthesis of these novel compounds. The key steps included an oxidative rearrangement of the protected d-glucose derivative 11 to afford the 1,4-dioxane 12, which could be elaborated to the coupling partner 5 and a photochemical [3 + 2]-cycloadditon between the 3-hydroxyflavone 27 and methyl cinnamate followed by base-induced alpha-ketol rearrangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 49 publications
1
78
0
Order By: Relevance
“…More specifically, this group demonstrated that silvestrol promotes aberrant interaction of mRNA with the RNA helicase eukaryotic initiation factor (eIF) 4A to prevent its productive association with eIF4F, thus inhibiting the initiation step of translation (86, 87). The structure of silvestrol was confirmed though total synthesis by two groups independently, namely, Porco, Jr. and co-workers at Boston University (88), and Rizzacasa and colleagues at the University of Melbourne in Australia (89, 90). The Rizzacasa group also prepared a biotinylated derivative of episilvestrol [the C-5"' epimer of silvestrol (81)], and showed this to be highly selective in binding eIF4A, further supporting this factor as the principal cellular target of silvestrol (79, 90).…”
Section: Examples Of Bioactive Compounds Isolated From Tropical Plantmentioning
confidence: 88%
“…More specifically, this group demonstrated that silvestrol promotes aberrant interaction of mRNA with the RNA helicase eukaryotic initiation factor (eIF) 4A to prevent its productive association with eIF4F, thus inhibiting the initiation step of translation (86, 87). The structure of silvestrol was confirmed though total synthesis by two groups independently, namely, Porco, Jr. and co-workers at Boston University (88), and Rizzacasa and colleagues at the University of Melbourne in Australia (89, 90). The Rizzacasa group also prepared a biotinylated derivative of episilvestrol [the C-5"' epimer of silvestrol (81)], and showed this to be highly selective in binding eIF4A, further supporting this factor as the principal cellular target of silvestrol (79, 90).…”
Section: Examples Of Bioactive Compounds Isolated From Tropical Plantmentioning
confidence: 88%
“…(−)-Silvestrol ( 35 ) was then achieved through a selective “double Mitsunobu ” reaction of (−)- epi -silvestrol ( 36 ). Future studies by Rizzacasa and coworkers disclosed a method to resolve racemic 191 using (−)-menthol, as well as an improved Mitsunobu coupling of 191 and 199 using (di-2-methoxyethyl azodicarboxylate) (137). …”
Section: Chemical Synthesis Of Cyclopenta[b]benzofuransmentioning
confidence: 99%
“…Aside from their complexity and synthetic challenge, silvestrol and epi -silvestrol displayed potent anticancer activity in A549 lung cancer proliferation assays with IC 50 values of 33 n M and 30 n M (137). The synthetic analogue 4′-desmethoxy- epi -silvestrol was also found to be highly potent against LIM1215 colon cancer cells proliferation with an IC 50 of 10 n M , foreshadowing the development of cytotoxic flavagline analogues that are more potent than their parent counterparts.…”
Section: Chemical Synthesis Of Cyclopenta[b]benzofuransmentioning
confidence: 99%
“…57 provided key advice and expertise in the preclinical evaluation strategy of silvestrol; J.C.B. assisted in experimental design and interpretation as well as critical reading of the paper, provided CLL patient samples, and is the co-principal investigator of the laboratory in which work was conducted; A.D.K.…”
mentioning
confidence: 99%